Reduced visual surround suppression in schizophrenia shown by measuring contrast detection thresholds - Serrano-Pedraza, Ignacio; Romero-Ferreiro, Verónica; Read, Jenny C. A.; Diéguez-Risco, Teresa; Bagney, Alexandra; Caballero-González, Montserrat; Rodríguez-Torresano, Javier; Rodriguez-Jimenez, Roberto (Frontiers in Psychology, 2014)
Visual perception in schizophrenia is attracting a broad interest given the deep knowledge that we have about the visual system in healthy population. In visual science it is known that the visibility of a grating located in the visual periphery is impaired by the presence of a surrounding grating of the same spatial frequency and orientation. Previous studies have suggested abnormal visual surround suppression in patients with schizophrenia. Given that schizophrenia patients have cortical alterations including hypofunction of NMDA receptors and reduced concentration of GABA neurotransmitter, which affect lateral inhibitory connections, then they should perform better than controls in visual suppression tasks. We tested this hypothesis by measuring contrast detection thresholds using a new stimulus configuration. We tested two groups: 21 schizophrenia patients and 24 healthy subjects. Thresholds were obtained using Bayesian staircases in a 4AFC detection task where the target was a grating within a 3 deg Butterworth window that appeared in one of four possible positions at 5 deg eccentricity. We compared three conditions, a) target with no surround (NS), b) target on top of a surrounding grating of 20 deg diameter and 25% contrast with same spatial frequency and orthogonal orientation (OS), and c) target on top of a surrounding grating with parallel (same) orientation (PS). Our results show significantly lower thresholds for controls than for patients in NS and OS conditions. We also found significant lower suppression ratios PS/NS in patients. Our results support the hypothesis that inhibitory lateral connections in early visual cortex are impaired in schizophrenia patients.